2012
DOI: 10.1016/j.diii.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging benign inflammatory syndromes

Abstract: Benign mastitis is a rare disease and its management is difficult. The diagnostic challenge is to distinguish it from carcinomatous mastitis. We make a distinction between acute mastitis secondary to an infection, to inflammation around a benign structure or to superficial thrombophlebitis, and chronic, principally plasma cell and idiopathic granulomatous mastitis. Imaging is often non-specific but we need to know and look for certain ultrasound, mammogram or magnetic resonance imaging (MRI) signs to give a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Many studies have shown that most cases of mastitis show a persistent or plateau pattern, which helps to differentiate the condition from malignant lesions [11] , [12] , [20] . In our study, breast cancer showed a washout pattern more frequently than inflammatory breast diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that most cases of mastitis show a persistent or plateau pattern, which helps to differentiate the condition from malignant lesions [11] , [12] , [20] . In our study, breast cancer showed a washout pattern more frequently than inflammatory breast diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory breast, sometimes referred to as red breast syndrome, is a classic but rare complaint in women consulting at gynecology emergency centers [ 1 , 2 ]. It usually presents as a red and hot breast and is often associated with breast pain [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced mastitis collections may present as round masses on ultrasound with surrounding hypervascularity. 29 Current guidelines recommend oral antibiotic treatment with continued breastfeeding to decrease engorgement. 30 Empiric treatment of S. aureus mastitis is usually with dicloxacillin or erythromycin in patients with penicillin allergies.…”
Section: Case #6: Mastitismentioning
confidence: 99%
“…Most commonly, it is caused by S. aureus but may also involve methicillin-resistant S. aureus and anaerobic organisms. 29 Clinical management of uncomplicated mastitis includes empiric antibiotic therapy, but unresolving infections even under antibiotic treatment warrants ultrasound diagnosis. Ultrasound examination of the affected breast is an appropriate initial imaging tool to look for possibilities of breast abscess or inflammatory breast disease which may have similar clinical presentations as mastitis.…”
Section: Case #6: Mastitismentioning
confidence: 99%